HOW CAN EMPLOYEE JOB INSECURITY BE REDUCED? THE ROLE OF RESPONSIBLE LEADERSHIP AND PSYCHOLOGICAL SAFETY (Third Sector Social Economic Review, 2025)
The paper aims to determine the mediating role of psychological safety under the effect of responsible leadership on employees' job insecurity.  The statistical data was obtained through a survey. The research sample consists of 388 white-collar employees in different sectors (education, health and finance). The mediator analysis test was used to test the research hypotheses. According to research findings, responsible leadership increases employees' psychological safety and reduces job insecurity while psychological safety reduces job insecurity. Additionally, it was found that psychological safety has a mediating role under the effect of responsible leadership on job insecurity.  It is also seen that the responsible leadership approach in organizations increases employees' psychological safety level and consequently reduces their job insecurity. Research findings and their implications are important in showing the factors that effectively ensure the continuity and effectiveness of employees in organizations.
Keywords: Responsible leadership; Psychological safety; Job insecurity; White-collars.